Bifurcation analysis based performance evaluation of power system incorporating FACTS controller - Marsadek M.; Mukerjee R.N.; Tanggawelu B.; Basha A.; Ariffin A.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
The major power system breakdowns are caused by problems relating to the system dynamic responses. The limiting factor in power system operation is the damping of oscillations. The damping torque provided by the FACTS device is proportional to the gain of the controller. A power system is highly nonlinear dynamical system, having always some influence on the controller performance. An inappropriate controller setting may cause interplay between controllers dispersed system wide, leading to evolution of nonlinear dynamic phenomena such as bifurcation. It is induced by variation in control gains and system parameters. For satisfactory system operation, appropriateness of each setting of the controller needs to be evaluated for a specific operating configuration. The in-depth evaluation of a controller setting leading to fine tuning of the controller gain is feasible through bifurcation analysis. 2003 IEEE.